More Than Just Words Training: Improving Student Organization Effectiveness - Aulia Ramdani; Chayrina Ramida Safitri; Frida Zakiyya Harasuna; Amatullah Mutmainna Musyaffa; Fiantika Lasmini; Septiani Cahyaningtyas; Nabila Aulia Rachman; Arindhira Putri Rianto; Muhammad Faiz Hermansyah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Miscommunication and a lack of transparency within the university student organization hindered coordination and fuelled internal conflicts. This project aimed to strengthen coordination and reduce conflict by enhancing the interpersonal communication competence of the organization members. After conducting a training needs analysis through questionnaires and interviews, psychology students partnered with HIMAHI to deliver a single session “More Than Just Words” workshop. Twelve student leaders attended four hours of interactive activities—including lecture‐style presentations, Q&A, ice breakers, and focus group discussions—embedded in the Industrial and Organizational Psychology practicum. Participants completed pre- and post-intervention assessments using the Interpersonal Communication Competence Questionnaire, and rated trainer performance via a structured satisfaction survey. Average declarative knowledge scores increased from 75.0% to 81.5%, reflecting an 8.7% gain. In the reaction survey, 75% of participants rated lecture clarity as “very good,” while 67% rated trainer mastery, engagement, and interactivity as “very good.” These outcomes demonstrate measurable improvements in communication knowledge and high participant satisfaction.